1992
DOI: 10.1017/s0022112092000387
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of non-spherical rebounding bubbles

Abstract: The motion of buoyant transient cavities with non-condensible contents is investigated numerically using a boundary-integral method. The bubble contents are described by an adiabatic gas law. Motion is considered in the neighbourhood of a rigid boundary, in an axisymmetric geometry. We investigate whether the non-condensible contents will resist the formation of jets. It is found that jets form upon collapse and, in general, completely penetrate the bubble before it rebounds, but circumstances are identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(73 citation statements)
references
References 17 publications
(23 reference statements)
3
69
1
Order By: Relevance
“…In the rigid fixed body case the bubble collapses without significant jet formation, then forms a very thin jet during rebound. Best & Kucera (1992) found similar results near solid walls. Lauterborn (1981) has observed jet formation during rebound using laser-generated bubbles.…”
Section: Deformation Effects On Jet Impact Loadssupporting
confidence: 62%
“…In the rigid fixed body case the bubble collapses without significant jet formation, then forms a very thin jet during rebound. Best & Kucera (1992) found similar results near solid walls. Lauterborn (1981) has observed jet formation during rebound using laser-generated bubbles.…”
Section: Deformation Effects On Jet Impact Loadssupporting
confidence: 62%
“…We consider an initially spherical bubble of radius 50 mm, located at a distance of X ¼ 1.5 mm from a flat material surface and subject it to a time-varying pressure field as represented in figure 2 and expressed as follows: This imposed pressure variation is different from that used in many classical studies on bubble collapse near a wall and where a bubble with a maximum radius is suddenly subjected to a pressure higher than the internal pressure such as in [71][72][73][74]. Here, bubble growth is included (this allows one to include standoff distances smaller than the bubble maximum radius and covers a large range of applications), and the time-varying pressure field represents for example the pressure encountered by a bubble nucleus captured in the shear layer of a cavitating jet.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Also, erosion and pit formation on surfaces caused by collapsing bubbles have been studied by correlating their dynamics with damage spots on the surface (Philipp and Lauterborn 1998;Isselin et al 1998;Tomita and Shima 1986). Numerical work on the interaction of a bubble with nearby boundaries using the boundary-integral method (Blake et al 1986;Best and Kucera 1992;Robinson et al 2001) has generally shown good agreement with experimental observations. Computations were performed up to the last stages of collapse (Best 1993;Zhang et al 1993;Brujan et al 2002) and beyond (Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%